Fatherhood and family values in Indonesia and Norway: A cross-cultural review - Keisha Kayla Shandy; Cipto Wardoyo (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2026)
This qualitative literature review compares how fathers shape family values in Indonesia and Norway. Guided by Hofstede’s cultural dimensions, this study synthesized literatures and policy reports to examine (1) fathers’ contributions to family values, (2) cross-cultural differences in paternal roles, and (3) the influence of societal norms and policies. Searches conducted in high-indexed journals from Scopus and Google Scholar by using combinations of keywords in both English and Indonesian. Inclusion and exclusion criteria, as well as screening procedures are detailed in Research Method. Thematic synthesis identified that in Indonesia, collectivist and patriarchal norms position fathers chiefly as providers and moral authorities, with involvement shaped by urban-rural location, socioeconomic status, and evolving gender norms. Meanwhile, in Norway, egalitarian culture and policies (e.g., the “father’s quota”) support shared caregiving and strengthen paternal bonds. Evidence on father absence and family disruption indicates risks for child socio-emotional outcomes. This study discuss implications for culturally sensitive parenting supports and policy design.